AN OVERVIEW OF NEW TRENDS IN THE COSMETICS INDUSTRY - JBOUR, NAWZAT D. AL (International Journal of Applied Pharmaceutics, 2025)
Cosmetic business is one of the major billers of the global economy since it serves a market which is growing up continuously due to different reasons such as consumer behavior changes, technological and scientific developments, in addition to the rise in consumer awareness. This review focuses on giving an idea about the importance of the cosmetics industry some details about how the change in the customer demands encourages innovation in this sector. Nowadays, the growing awareness of the clean beauty is considered a trend, where the chemical-free, ethical, and sustainable products are of higher interest for most customers. It is worth to mention that the industrial practices for cosmetics are changing due to the developing personalized skincare and haircare products, as well as, environmentally friendly packaging, and the use of artificial intelligence in product creation and promotion. This review focuses on the use of nanotechnology in cosmetics and dermatology products. The use of nanotechnology helped in improving the active components' stability, penetration, and effectiveness. Particularly useful for sun protection anti-aging treatments, in addition to the targeted administration of active ingredients such as Nano emulsions, liposomes, and nanoparticles. This review offers a detailed information about the recent developments and trends in the cosmetics industry, focusing on how nanotechnology could be used to meet the changes in consumer needs taking into consideration sustainability and safety issues.